New Architecture of ZnGeN2/In0.16Ga0.84N Type‐II Quantum Well‐Based Green Emitting LED. Issue 8 (8th May 2018) - Rolles, Mélanie; Hyot, Bérangère; Miska, Patrice
Abstract : We report here on a new green‐emitting light emitting device (LED) architecture containing only 16% of indium. The structure is based on the use of a new type‐II ZnGeN2 /In0.16 Ga0.84 N quantum well. The zinc germanium nitride (ZnGeN2 ) is a new promising semiconductor for optoelectronic devices such as LEDs or photovoltaic cells due to its large, direct, and adjustable band gap, most particularly considered to overcome the green‐gap issue in LED technology. Studies of ZnGeN2 ‐based quantum well behaviors are scarce and no information on the overall electro‐optical operation of such LED is available. We simulate here the complete behavior of a green LED structure in which the active region is a type‐II ZnGeN2 /In0.16 Ga0.84 N quantum well. A thin AlGaN layer is used as a barrier for a better carrier confinement. The position and the thickness of the ZnGeN2 layer are parameters used to examine the luminous and electrical behavior as well as the external quantum efficiency of this LED compared to a standard In0.22 Ga0.78 N LED emitting at the same wavelength. We demonstrate a significant enhancement of the spontaneous emission and the possibility to reach both a better quantum efficiency and light output when using the type‐II structure. Abstract : The authors report the opto‐electrical characterisation of a new green‐emitting light emitting device (LED) structure based on ZnGeN2 /InGaN type‐II quantum well. This LED shows a better spontaneous emission, a higher external quantum efficiency (EQE), and luminous output power, compared to the standard InGaN/GaN green LED.